2000
DOI: 10.2174/1381612003400128
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Vitamin D Analogs

Abstract: Within the past decade it has been shown that psoriasis can be treated topically with analogs of vitamin-D3. Impaired differentiation and increased proliferation of keratinocytes are key features in psoriatic lesions together with a local activation of T lymphocytes. Evidence has accumulated showing that analogs of vitamin D3 increase differentiation and inhibit proliferation of keratinocytes. Therefore, analogs of vitamin D3 have been investigated in a number of trials showing improvement of psoriasis. It has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 49 publications
(77 reference statements)
0
21
0
2
Order By: Relevance
“…Several studies have shown that calcipotriol as well as calcitriol and tacalcitol are efficacious, safe and can be used on a long-term basis for psoriasis (43,(46)(47)(48)(49). Vitamin D3 analogs can be used in combination with phototherapy(50).…”
Section: Effects Of Vitamin D3 Analogues In Psoriasismentioning
confidence: 99%
“…Several studies have shown that calcipotriol as well as calcitriol and tacalcitol are efficacious, safe and can be used on a long-term basis for psoriasis (43,(46)(47)(48)(49). Vitamin D3 analogs can be used in combination with phototherapy(50).…”
Section: Effects Of Vitamin D3 Analogues In Psoriasismentioning
confidence: 99%
“…This analogue appears to be equipotent with 1,25(OH) 2 D 3 in inhibiting the growth of MCF-7 breast cancer cells in vitro (Colston et al 1992a), but displays calcaemic activity 100-200 times less than the natural hormone. This profile of activity was subsequently found to be largely due to rapid inactivation of the analogue in vivo and subsequently this compound has been developed and marketed for topical treatment of psoriasis (Binderup & Kragballe 1992, Fogh & Kragballe 2000. With regard to breast cancer, the efficacy of topical treatment of cutaneous nodules with calcipotriol has been investigated (Bower et al 1991).…”
Section: Calcipotriol (Mc903)mentioning
confidence: 99%
“…1,25(OH) 2 D 3 and its analogs have been shown to inhibit autoimmune diseases in animal models, such as experimental allergic encephalomyelitis (14 -16), murine lupus (17), collagen-induced arthritis (18,19), and type 1 diabetes (20). They are clinically used in the treatment of psoriasis, a Th1-mediated autoimmune disease of the skin, where they show efficacy comparable to topical steroids (21). Polymorphisms of the vitamin D receptor gene have been associated with type 1 diabetes in different populations (22,23).…”
mentioning
confidence: 99%